Developing games with Magic Playground: A gesture-based game engine - Rodrigo Sacadura; Dehanov, J.; Dias, J.; Bastos, R. (ACE '05: Proceedings of the 2005 ACM SIGCHI International Conference on Advances in computer entertainment technology, 2005)
This paper presents Magic Playground, a game engine that enables the development of entertainment applications with real-time gesture-based Human-Computer Interaction (HCI). We describe the main architectural elements of our system and provide a guideline on how to program the engine to create games. Finally, we present the usability evaluation results of a game which emulates the known Tetris game.